METODE POST DISASTER NEED ASSESSMENT (PDNA) DALAM EVALUASI KELAYAKAN GEDUNG NEGARA : STUDI KASUS GEDUNG BPBD KOTA PAGAR ALAM - Norma Puspita (Jurnal Tekno Global, 2018)
Mountain topography makes Pagar Alam City is highly prone to natural disasters such as landslides, floods, tornados, and volcanoes, as well as disasters due to of human negligence such as forest fires, land and houses fires. According to it, the government building development so that the State must be able to support implements selected BPBDs main tasks and functions as the regional disaster management agencies. In planning the building of the State, one of the stages that must be met is the study. This study aims to evaluate the economic feasibility of investment in buildings State based disaster loss assessment using the Post Disaster Need Assessment. The result of investment analysis shows a positive NPV IRR> discount rate, the building of the State BPBDs feasible to continue. Keywords : PDNA, mitigation, the feasibility of government building.